In vitro cariostatic effects of various iron supplements on the initiation of dental caries - Thakib A. Al-Shalan (Elsevier, 2009)
Previous animal and laboratory studies have shown the possible cariostatic effect of iron. The purpose of this study was to in vitro study the effect of different concentrations of four iron supplements on the initiation of dental caries.Materials and methods: Four products of iron supplements were used namely fre-in-sol, ferotonic, feromin and ferose. Two hundred extracted teeth were distributed randomly into 10 groups. Eight groups were from the four iron products in two concentrations (100% and 50%) in addition to the positive and negative control groups. Mutans streptococci bacteria (6715) grown in Todd Hewitt Broth were used. Assessment of decalcification and cavitation was done daily for 60 days.Results: It showed that different iron - supplement products play cariostatic effect in the initiation of the dental caries. With the exception of 100% and 50% ferose, both 100% and 50% concentrations of all supplements have cariostatic effect. The mean dates for decalcification varied with lowest for the positive control (12.2 days) and the highest was for 50% feromin. Cavitation was seen in the positive control and 100% ferose groups with mean on the first day of cavitation of 57 days.Conclusion: It was concluded that iron may have cariostatic effect on the in vitro development of dental caries in human teeth.